Odor-active aroma compounds in traditional fermented dairy products: The case of mabisi in supporting food and nutrition security in Zambia - Thelma W. Sikombe; Anita R. Linnemann; Himoonga B. Moonga; Stefanie Quilitz; Sijmen E. Schoustra; Eddy J. Smid; Anna Alekseeva (Current Research in Food Science)
Aroma is a key sensory attribute that determines consumer preference and acceptability of foods. The aroma of fermented dairy products comprises the volatile organic compounds (VOCs) produced by the activity of fermenting microbes and the compounds originally present in unfermented raw milk. A unique combination of specific compounds detectable by human olfactory senses creates the distinct odor profile of fermented products. This study investigated the influence of different production methods on the VOCs responsible for the odor-active compounds, and the microbial communities present in mabisi, a traditional Zambian fermented dairy product. The VOCs and microbial community composition of four mabisi variants were investigated using GC-O-MS and PTR-QiTOF-MS techniques, and 16S rRNA amplicon sequencing, respectively. A panel of three assessors identified the odor-active compounds from the GC-O-MS, and the compound's quantitative aspects were obtained by the PTR-QiTOF-MS.Twelve volatile compounds were identified as odor-active compounds during the GC-O-MS analysis. The most prominent were ketones and esters, which imparted a buttery and fruity aroma, respectively. The PTR-QiTOF-MS run identified and quantified a total of 390 m/z peaks, 55 of which were tentatively identified. 16S rRNA amplicon sequencing revealed a diverse microbial community, with Lactococcus species dominating. While the VOC profiles showed significant variation in functionality among the variants, minor differences were observed in microbial composition.The study confirms that high compound concentration does not necessarily correlate with compound odor activity. Our findings offer insights into the significance of aromas and microbial ecology to support optimization strategies for upscaling traditional fermented products.